Metabolically Abnormal But Normal-Weight Individuals Had a Higher Risk of Type 2 Diabetes Mellitus in a Cohort Study of a Chinese Population - Chen, Qiannan; Zhou, Yaohan; Dai, Chen; Zhao, Gang; Zhu, Yimin; Zhang, Xuhui (Frontiers in Endocrinology, 2021)
Aims: Obesity is a heterogeneous disease in terms of body mass index (BMI) and metabolic status. The purpose of this study was to investigate the risk of type 2 diabetes mellitus (T2DM) in subjects with metabolically abnormal but normal weight (MANW) in China. Materials and Methods: A prospective cohort with a total of 17,238 participants of the Zhejiang metabolic syndrome cohort was recruited. According to the standard of the Working Group on Obesity in China, general obesity is defined. Metabolic abnormality was defined as two or more abnormal components (elevated triglycerides (TG), low high-density lipoprotein cholesterol (HDL-C), elevated systolic blood pressure (SBP) or diastolic blood pressure (DBP) or use of antihypertensive therapy, and elevated fasting plasma glucose or anti-diabetic treatment). The hazard ratio (HR) and its 95% confidence interval (CI) were calculated using a multiple regression model, adjusted for the potential confounding factors. Results: Compared with metabolically normal and normal weight (MNNW) subjects, the metabolically abnormal and obesity/ overweight (MAO) subjects had the highest risk of T2DM disease, with an HR of 4.67 (95% CI: 3.23 - 6.76), followed by MANW subjects (HR=2.61, 95% CI=1.74 - 3.92) and MNO subjects (HR=2.09, 95% CI=1.29 - 3.38) after adjusted for age, sex, smoking, drinking, physical activity and family history of diabetes. Compared with MNNW, the HR in MANW subjects was significantly higher than that in metabolically normal but overweight/obesity (MNO) subjects. In normal-weight subjects, the HR of T2DM was significantly positively correlated with the number of components with metabolic abnormalities. Conclusions: MANW subjects had a higher risk of T2DM. MANW subjects should be given more attention in the prevention and control of common chronic diseases. Key words: obesity, heterogeneity, type 2 diabetes mellitus, metabolically abnormal but normal weight (MANW), metabolically normal but overweight/obesity (MNO).